Efficient metal-free organic room temperature phosphors - Nidhankar, Aakash D.; Goudappagouda; Wakchaure, Vivek C.; Babu, Sukumaran Santhosh (Chemical Science, 2021)
An innovative transformation of organic luminescent materials in recent years has realised the exciting research area of ultralong room-temperature phosphorescence. Here the credit for the advancements goes to the rational design of new organic phosphors. The continuous effort in the area has yielded wide varieties of metal-free organic systems capable of extending the lifetime to several seconds under ambient conditions with high quantum yield and attractive afterglow properties. The various strategies adopted in the past decade to manipulate the fate of triplet excitons suggest a bright future for this class of materials. To analyze the underlying processes in detail, we have chosen high performing organic triplet emitters that utilized the best possible ways to achieve a lifetime above one second along with impressive quantum yield and afterglow properties. Such a case study describing different classes of metal-free organic phosphors and strategies adopted for the efficient management of triplet excitons will stimulate the development of better candidates for futuristic applications. This Perspective discusses the phosphorescence features of single- and multi-component crystalline assemblies, host-guest assemblies, polymers, and polymer-based systems under various classes of molecules. The various applications of the organic phosphors, along with future perspectives, are also highlighted.

Excimer to exciplex transition through realization of donor-acceptor interactions in luminescent solvent-free liquids - Wakchaure, Vivek Chandrakant; Goudappagouda; Das, Tamal; Ravindranathan, Sapna; Babu, Sukumaran Santhosh (Nanoscale, 2021)
Luminescent solvent-free organic liquids are known for their enhanced quantum yield, color tunability, and availability of a matrix for other dopants to generate hybrid luminescent materials with improved features for newer applications. Herein, we report a donor-acceptor based luminescent ``exciplex liquid'' by utilizing the slightly different electron affinity of the acceptor molecules. A red-shifted broad exciplex emission exhibited by the donor-acceptor pair even at a lower concentration of the acceptor (0.001 equiv.) indicates high efficiency in the solvent-free state. A detailed NMR study revealed weak intermolecular interactions between the donor and acceptor in the solvent-free matrix that stabilizes the exciplex liquid. The failure of structurally similar solid counterparts to form an exciplex confirms the advantage of the available supportive liquid matrix. Besides, the luminescent exciplex liquid is found efficient in sensing application, which is unachievable by either the individual liquids or their solid counterparts. Here, a transition of a donor-acceptor pair from a solid to solvent-free liquid results in a new hybrid liquid that can be an alternative for solid sensor materials.